PENERAPAN SCAFFOLDING DALAM MATA PELAJARAN PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN MATERI ATURAN DI RUMAH KELAS II DI SDN POLISI 2 BOGOR - Anggi Nurfitriani; Mursidah Rahmah; Riksa Suci Imaniah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to describe the application of scaffolding in Pancasila and Citizenship Education, home rule material for class II at SDN Polisi 2 Bogor. The research method used is descriptive qualitative with data collection techniques including interviews, observation, and documentation. The results of the research show that learning in the subjects of Pancasila and Citizenship Education, home rule material through a learning process that applies the Culturally Responsive Teaching (CRT) approach, the Problem Based Learning (PBL) model, and the lecture, question and answer, assignment and discussion methods can certainly attract attention. learners. Meaningful learning can be created through problem-based learning because it involves students solving real-world problems, encouraging higher-order thinking skills. Meaningful learning can help develop students' independence and self-confidence. Thus, problem-based learning can make a significant contribution to creating a more meaningful learning experience for students.